The impact of the formal employment contract on credit access in Africa - (:unkn) unknown (My University, 2020)
Utilizing a new database of over 200 employees surveyed in Senegal, we demonstrate the impact of formalization and employment contracts on credit access. Through a probit model, we show that formalization has a significantly positive impact on credit access since an employee's probability of accessing credit increases by 23% if they have a formal employment contract. The possession of an employment contract increases the likelihood of having a bank account by 18%. We find that other potential determinants studied in the existing literature, such as gender, education and salary, do not have a significant impact on access to credit. These results highlight the impact of formalization on credit access and make a strong case for the economic development that could result from a continuation of the efforts being undertaken to formalize African economies, which still remain predominantly informal.
Keywords: African Research